Under sentence of death : lynching in the South - Brundage, W. Fitzhugh (William Fitzhugh), 1959- (Chapel Hill ; London : The University of North Carolina Press, 1997)
This collection of essays explores "such topics as same-race lynchings, black resistance to white violence, and the political motivations for lynching ... The book raises important questions about Southern history, race relations, and the nature of American violence."--Page 4 of cover.
Narrative and event : lynching and historical sociology / Larry J. Griffin, Paula Clark, Joanne C. Sandberg -- Sociogenesis of lynching / Roberta Senechal de la Roche -- Most unexampled exhibition of madness and brutality : Judge Lynch in Saline County, Missouri / Thomas G. Dyer -- Lynching in wartime Carolina : the death of Saxe Joiner / Joan E. Cashin -- When race didn't matter : black and white mob violence against their own color / E.M. Beck, Stewart E. Tolnay -- Gender, sexuality, and politics of lynching : the Leo Frank case revisited / Nancy MacLean -- Lynching and political power in Mississippi and South Carolina / Terence Finnegan -- North Carolina lynching ballads / Bruce E. Baker -- By the book : the legal executions of Kentucky blacks / George C. Wright -- Roar on other side of silence : black resistance and white violence in American south, 1880-1940 / W. Fitzhugh Brundage -- Unsettled business : Ida B. Wells against lynching, or, how antilynching got its gender / Patricia A. Schechter.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Online resource (HeinOnline, viewed August 4, 2021).
Keywords: Lynching -- Southern States -- History; African Americans -- Crimes against -- History; Southern States -- Race relations -- History; Racism -- Southern States -- History; Lynchage -- États-Unis (Sud) -- Histoire; Noirs américains -- Crimes contre -- Histoire; Racisme -- États-Unis (Sud) -- Histoire; États-Unis (Sud) -- Relations raciales -- Histoire; TRUE CRIME -- General; African Americans -- Crimes against; Lynching; Race relations; Racism; Southern States; Lynchjustiz; Geschichte; Aufsatzsammlung; USA -- Südstaaten; Lynchen; Criminology, Penology & Juvenile Delinquency; Social Welfare & Social Work; Social Sciences; Lynchage -- États-Unis (sud); Noirs américains -- Crimes contre -- États-Unis.; Racisme -- États-Unis (sud); États-Unis (sud) -- Relations interethniques; History